É possível identificar a dengue em crianças a partir do critério de caso suspeito preconizado pelo Ministério da Saúde? Is it possible to identify dengue in children on the basis of Ministry of Health criteria for suspected dengue cases? - Marisa B. P. Rodrigues; Heliane B. M. Freire; Paulo R. L. Corrêa; Marislaine L. Mendonça; Maria Regina I. Silva; Elizabeth B. França (Elsevier, 2005)
OBJETIVOS: Identificar características clínicas indicativas de dengue e avaliar a aplicabilidade, na criança, do critério de caso suspeito do Ministério da Saúde. MÉTODOS: Estudo transversal, realizado no Centro Geral de Pediatria, Fundação Hospitalar de Minas Gerais. Foram incluídas crianças com doença febril aguda sem etiologia definida, com duração > 24 horas e < 7 dias, procedentes da Região Metropolitana de Belo Horizonte. Foram investigadas variáveis clínicas, realizados exames específicos e dosagem de aspartato-aminotransferase, em período considerado endêmico e epidêmico da doença. O grupo de crianças com dengue foi comparado com o grupo com doenças febris agudas inespecíficas. O critério de caso suspeito do Ministério da Saúde foi avaliado. RESULTADOS: O diagnóstico de dengue foi feito em 50,4% das 117 crianças incluídas no estudo. Não houve associação estatisticamente significativa entre a doença e a maioria dos sintomas analisados. Somente o exantema associou-se mais à dengue (Razão de Prevalência = 1,49; IC a 95%: 1,05-2,11). A sensibilidade do critério de caso suspeito de dengue foi de somente 50,8%, e o valor preditivo positivo de 62,5%. Esses valores foram maiores nos escolares e no período de maior incidência da doença. CONCLUSÕES: A dengue é freqüente entre as doenças febris na infância, com prevalência variando de acordo com a situação epidemiológica. A clínica das crianças com dengue foi muito semelhante à das crianças com outras doenças inespecíficas. O critério de caso suspeito do Ministério da Saúde mostrou-se de pouca utilidade, principalmente nas crianças menores e em períodos de menor incidência. OBJECTIVES: To identify clinical characteristics indicative of dengue and to evaluate the applicability to children of the Health Ministry criteria for suspected cases. METHODOS: A cross-sectional study undertaken at the General Pediatrics Center of the Fundação Hospitalar de Minas Gerais. Children were enrolled if presenting acute febrile conditions with no definite etiology, lasting > 24 hours and < 7 days and if resident in the Metropolitan Region of Belo Horizonte. Clinical variables were investigated, specific tests were performed and aspartate-aminotransferase assayed, during a period considered both endemic and epidemic for the disease. The subset of children who did have dengue was compared with the subset of nonspecific acute febrile diseases. The Health Ministry criteria for suspected cases was evaluated. RESULTS: Dengue was diagnosed in 50.4% of the 117 children studied. There were no statistically significant associations between the disease and the majority of the symptoms analyzed. Only exanthema was more often associated with dengue (Prevalence Ratio = 1.49; 95% CI: 1.05-2.11). The criteria for suspected cases of dengue had a sensitivity of just 50.8% and a positive predictive value of 62.5%. These values were greater among schoolchildren and during the period of greater disease incidence. CONCLUSIONS: Dengue is common among febrile diseases of childhood, with prevalence that varies according to the epidemiological situation. The clinical status of children with dengue was very similar to that of children with other nonspecific diseases. The Health Ministry criteria for suspected cases were shown to be of little use, particularly with smaller children and during periods of reduced incidence.